Reação de maracujazeiros e figueiras ao nematoide das galhas - Costa, Marylia Gabriella Silva [UNESP] (2014)
This Fruit growing has great economic and social importance in Brazil, is present in all states of the country, is one of the activities that most consolidates generating employment, income, and rural development in agribusiness. Among the phytosanitary problems of fruit plants, nematodes stand out, because the damage caused by them. Given the importance of nematodes in fruit and unwieldy, since they are perennial crops, the present study aimed to evaluate the reaction of varieties of fig and passion fruit genotypes to Meloidogyne incognita, M. javanica and M. enterolobii. The experiments were conducted in a greenhouse for 120 days. The infestation of the substrate was performed with 5000 eggs of the nematode for each species. The tomato ‘Rutgers’ was used as the standard of viability of inoculum. The variables evaluated were: gall index, egg mass index and nematode reproduction factor. All fig genotypes behaved as susceptible to M. incognita, M. javanica and M. enterolobii. The passion fruit genotypes were resistant to three species of nematodes, except Roxinho do Kênia, who behaved as susceptible to M. incognita, M. javanica and M. enterolobii.